A new frontier in temporomandibular joint osteoarthritis treatment: Exosome-based therapeutic strategy - Yuan, Wenxiu; Wu, Yange; Huang, Maotuan; Zhou, Xueman; Liu, Jiaqi; Yi, Yating; Wang, Jun; Liu, Jin (Frontiers in Bioengineering and Biotechnology, 2022)
Temporomandibular joint osteoarthritis (TMJOA) is a debilitating degenerative disease with high incidence, deteriorating quality of patient life. Currently, due to ambiguous etiology, the traditional clinical strategies of TMJOA emphasize on symptomatic treatments such as pain relief and inflammation alleviation, which are unable to halt or reverse the destruction of cartilage or subchondral bone. A number of studies have suggested the potential application prospect of mesenchymal stem cells (MSCs)-based therapy in TMJOA and other cartilage injury. Worthy of note, exosomes are increasingly being considered the principal efficacious agent of MSC secretions for TMJOA management. The extensive study of exosomes (derived from MSCs, synoviocytes, chondrocytes or adipose tissue et al.) on arthritis recently, has indicated exosomes and their specific miRNA components to be potential therapeutic agents for TMJOA. In this review, we aim to systematically summarize therapeutic properties and underlying mechanisms of MSCs and exosomes from different sources in TMJOA, also analyze and discuss the approaches to optimization, challenges, and prospects of exosome-based therapeutic strategy.